Does Efficient Management of Working Capital have a Parallel Impact on the Profitability of Small and Large Firms? - Afeef, Mustafa; Takreem, Kausar; Bakhsh Baloch, Qadar (The Journal of Humanities & Social Sciences, 2023)
Working Capital Management has an overriding impact on a firm’s profit performance. However, the profitability of large firms, unlike small ones, might show a different degree of sensitivity to the efficient management of working capital. One wonders as to which category of firms (small or large) exhibit more escalation in their profitability as a result of a decent management of their working capital. Exploring the answer to this query is the foremost aim of the present work. To investigate, effect of working capital management was determined on profitability of small and large organizations separately and their results were compared. Findings from the comparison suggested that indicators of working capital management had a more perceptible impact on profitability of firms of relatively larger size. It is, thus, suggested for managers of large-sized corporations to redouble their thought on effective and vigilant management of their working capital so as to invigorate profitability.